Mass spawning by the date mussel Lithophaga lithophaga - Ante Žuljević (Nature Portfolio, 2018)
Abstract Lithophaga lithophaga is one of the commonest bivalves in the Mediterranean Sea and is present in almost every subtidal calcareous rock. Its reproductive cycle is known only from laboratory studies. Herein, we present data on the species reproductive activities based on localised but mass synchronized spawning events. The species reproduces at the end of the northern hemisphere summer and the majority of significant spawning events occur during the period between full moon and its last quarter. Calm seas are an important pre-requisite for the development of such co-ordinated mass spawning events. ‘Gamete to gamete’ induction seems to be the most likely proximate cue in synchronising gamete release. Spawning begins with a few individuals but spreads progressively along the coastline. In observed situations, reproductive waves finally affect between 10 and >400 m of coastline from 0 to 10 m depth and last longer than three days. In the reproductive zone, dense gamete clouds reduce visibility to zero over tens of metres along the shallow sea bed. No spawning events of such dimensions have been reported upon before for any bivalve.